Does Acetabular Inclination Angle Affect Survivorship of Alumina-ceramic Articulations? - Johansson, Henning R. (Springer-Verlag, 2010)
BACKGROUND: Reports in the literature have linked high acetabular inclination angles to increased wear of ceramic-on-ceramic bearings. However, many of these studies were only conducted in vitro and did not address the clinical relevance of such findings. QUESTIONS/PURPOSES: We therefore determined: (1) whether the cup inclination angle influences survival or function in patients with ceramic-on-ceramic implants; (2) the incidence of radiolucencies, osteolysis, and subsidence of ceramic-on-ceramic implants; and (3) whether the survival rate higher for ceramic-on-ceramic THAs than for conventional metal-on-polyethylene THAs. METHODS: We retrospectively reviewed 537 THAs performed in 512 prospectively followed patients having THA between October 1996 and October 2000. Eleven patients (12 hips) were lost to followup before 2 years, leaving 501 patients (525 THAs); of these, 421 were alumina ceramic-on-ceramic articulations and 104 cobalt-chromium-on-polyethylene. The mean age was 54 years. We determined acetabular cup inclination angles, Harris hip scores, Health-Status-Questionnaire-12 scores, and presence and location of any radiolucencies, osteolysis, or radiographic subsidence. We compared survival using the Kaplan-Meier method. The minimum followup was 24 months (mean, 59 months; range, 24–120 months). RESULTS: Twenty-two of the 424 THAs (4.2%) were revised. We observed no difference in clinical or radiographic outcomes with respect to cup inclination angles. Radiographically, two loose acetabular components and two femoral components had subsided. The 5-year survival rate was slightly higher for ceramic-on-ceramic bearings (98%) than for metal-on-polyethylene (92%). CONCLUSIONS: Although there may be a link between acetabular inclination angles and wear rates as reported by some authors, we found no differences in patient function or radiographic survivorship using alumina-on-alumina articulations. LEVEL OF EVIDENCE: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.